A Better Life for All? Democratization and Electrification in Post-Apartheid South Africa - (:unkn) unknown (My University, 2016)
Does democracy affect basic service delivery? If yes, who benefits, and which elements of democracy matter - enfranchisement, the lib-eralization of political organization, or both? In 1994, 19 million South Africans gained the right to vote. The previously banned African National Congress was elected promising “a better life for all”. Using a difference-in-differences approach, we exploit heterogeneity in the share of newly enfranchised voters across municipalities to evaluate how franchise extension affected household electrification. Our unique dataset combines nightlight satellite imagery, geo-referenced census data, and municipal election results from the 1990s. We include covariates, run placebo regressions, and examine contiguous census tracts. We find that enfranchisement increased electrification. In parts of the country where municipalities lacked distribution capacity, the national electricity company prioritized core constituencies of the ANC. The effect of democratization on basic services depends on the national government’s ability to influence distribution at the local level.
Keywords: African Research